2019
DOI: 10.4103/ijmr.ijmr_1896_17
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on erlotinib & gefitinib therapy in non-small cell lung carcinoma patients

Abstract: Background & objectives:Tyrosine kinase inhibitors (TKIs) targeting the epidermal growth factor receptor (EGFR) have been evaluated in patients with advanced non-small cell lung cancer (NSCLC). Erlotinib and gefitinib are the first-generation EGFR-TKIs for patients with NSCLC. However, there is a paucity of studies comparing the effectiveness of these two drugs. Hence, this study was aimed to compare the effectiveness and safety of erlotinib and gefitinib in NSCLC patients.Methods:This study included 71 NSCLC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The high expression of LINC00973 was associated with poor prognosis in NSCLC patients, which indicated that LINC00973 might act as a carcinogen in the progression of NSCLC. As we all know, gefitinib and erlotinib were common anti-cancer drugs for lung cancer ( 26 , 27 ), and Gefitinib and erlotinib could reduce the expression of carcinogenic LINC00973, which was expected to improve the prognosis of lung cancer patients. Therefore, LINC00973 might be a promising target for the development of new therapies for NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…The high expression of LINC00973 was associated with poor prognosis in NSCLC patients, which indicated that LINC00973 might act as a carcinogen in the progression of NSCLC. As we all know, gefitinib and erlotinib were common anti-cancer drugs for lung cancer ( 26 , 27 ), and Gefitinib and erlotinib could reduce the expression of carcinogenic LINC00973, which was expected to improve the prognosis of lung cancer patients. Therefore, LINC00973 might be a promising target for the development of new therapies for NSCLC.…”
Section: Discussionmentioning
confidence: 99%